2020
DOI: 10.1113/jp280309
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal enteric neurons of the cavine distal colon are sensitive to hypoosmolar stimuli

Abstract: Neurons of the enteric submucous plexus are challenged by osmolar fluctuations during digestion and absorption of nutrients. r Central neurons are very sensitive to changes in osmolality but knowledge on that issue related to enteric neurons is sparse. r The present study focuses on investigation of osmosensitivity of submucosal neurons including potential molecular mediating mechanisms. r Results show that submucosal neurons respond to hypoosmolar stimuli with increased activity which is partially mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
(136 reference statements)
0
9
1
Order By: Relevance
“…11 A number of studies suggest an important role for TRPV4 in the regulation of gastric motility and emptying. 70 In the colon, the channel is thought to play diverse roles in osmosensation 6,71 and regulation of barrier function, 56 with possible implications for diseases such as ulcerative colitis. 72 In the current study, the largest amount of mRNA for TRPV4 was found in the mucosa of the stomach (cardia and fundus; Figure 1D).…”
Section: Discussionmentioning
confidence: 99%
“…11 A number of studies suggest an important role for TRPV4 in the regulation of gastric motility and emptying. 70 In the colon, the channel is thought to play diverse roles in osmosensation 6,71 and regulation of barrier function, 56 with possible implications for diseases such as ulcerative colitis. 72 In the current study, the largest amount of mRNA for TRPV4 was found in the mucosa of the stomach (cardia and fundus; Figure 1D).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Kollmann et al . (2020) additionally provides the first hints for the signal mechanism involved in osmosensation by enteric neurons as their pharmacological approaches – supported by the proof of expression on the mRNA level via qPCR – clearly indicate that TRPV4 plays an essential role in the reception mechanism. TRPV4 is a polymodal ionotropic receptor (Kumar et al .…”
mentioning
confidence: 86%
“…In this issue of The Journal of Physiology , Kollmann et al . (2020) describe the response of submucosal neurons to hypoosmolar stimuli. Depending on the amplitude of the decrease in osmolarity, up to about one tenth of these neurons reacted with an action potential discharge concomitant with an increase in the cytosolic Ca 2+ concentration when exposed to a locally applied puff of a hypotonic solution.…”
mentioning
confidence: 99%
See 2 more Smart Citations